2013
DOI: 10.1111/jcpp.12188
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brainstem dysfunction after preterm birth predicts behavioral inhibition

Abstract: Background: Behavioral inhibition (BI), the tendency to withdraw or exhibit negative affect when experiencing stressful situations, is a major risk factor for the development of social anxiety. However, neonatal biologic origins of this progression are still unknown. Click here to enter text.This study aimed to extend frameworks of behavioral inhibition by exploring empirically the central role of neonatal brainstem electrophysiologic functions in the development of social disengagement and BI. Methods: Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
(67 reference statements)
5
24
0
Order By: Relevance
“…In future, it will be interesting to investigate this question in more detail in order to ascertain whether there is an optimum level between over‐ and understimulation (cf Gardner & Karmel, ; Kidd, Piantadosi, & Aslin, ) and how this differs between individuals. This may relate to previous research that has investigated early individual differences in infants’ preferences for high and low external stimulation from both a state (Gardner & Karmel, ; Geva, Gardner, & Karmel, ) and trait (Cohen et al., ; Gardner, Karmel, Magnano, Norton, & Brown, ; Gardner et al., ; Geva, Schreiber, Segal‐Caspi, & Markys‐Shiffman, ) perspective.…”
Section: Discussionmentioning
confidence: 84%
“…In future, it will be interesting to investigate this question in more detail in order to ascertain whether there is an optimum level between over‐ and understimulation (cf Gardner & Karmel, ; Kidd, Piantadosi, & Aslin, ) and how this differs between individuals. This may relate to previous research that has investigated early individual differences in infants’ preferences for high and low external stimulation from both a state (Gardner & Karmel, ; Geva, Gardner, & Karmel, ) and trait (Cohen et al., ; Gardner, Karmel, Magnano, Norton, & Brown, ; Gardner et al., ; Geva, Schreiber, Segal‐Caspi, & Markys‐Shiffman, ) perspective.…”
Section: Discussionmentioning
confidence: 84%
“…The few studies measuring ABR in children born preterm at later ages -1 to 8 yearsconcluded that there is no significant difference with term-born children at those ages. 37 They used ABR measurement to determine whether an infant had normal or compromised brainstem function, and concluded that compromised brainstem function canalized behavioural inhibition in children born preterm at 12 months of age. Exposure to the extra-uterine environment in the third trimester of pregnancy slows down the myelination process, which is responsible for rapid synchronized conduction along the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Brainstem input mediates early social behavior. This is evident by its effects on gaze engagement (Geva et al., ), affective responses (Shinya, Kawai, Niwa, & Myowa‐Yamakoshi, ), vagal tone regulation (Porges, Doussard‐Roosevelt, Portales, & Greenspan, ), and initiation of social responses at infancy (Geva, Schreiber, Segal‐Caspi, & Markus‐Shiffman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Brainstem connectivity to the limbic circuit supports emotional signaling and affect sharing (Porges, ; Prechtl, ; Tucker et al., ), social gaze engagement (Geva et al., ), and initiation of social regulation strategies (Geva et al., ). These relations suggest a potential role for brainstem‐related pathways, which mature at late term age, in setting a time‐sensitive window for later maturing limbic‐cortical neural networks that enable social attention (Doesburg et al., ; Geva & Feldman, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation